The Development of Critical Thinking Skills during Practical Training: The Perspectives of Pedagogical Supervisors and Sports and Physical Education Trainees - Nziengui Nsonde, Beralex Vianney; Mandoumoou, Paulin; Kpazaï, Georges (European Scientific Journal, ESJ, 2024)
In the Republic of Congo, formal teacher training is comprised of both theoretical and practical components. Theoretical training takes the form of theoretical courses within the training institution itself. On the other hand, practical training takes place in professional settings such as secondary school. The purpose of this comparative study was to identify the conceptions of critical thinking development held by pedagogical supervisors and student trainees. Rooted in a qualitative methodological approach, this research was based on Eric Lavertu’s (2013) conceptual approach to the development of critical thinking during internships. Eight (08) pedagogical supervisors and nineteen (19) student-interns voluntarily participated in the study via focus groups. The results revealed a categorization of several didactic-pedagogical devices for the development of student-interns’ critical thinking, according to both the pedagogical supervisors and the student-interns themselves. To foster the development of critical thinking in student trainees, the devices mentioned specify that the supervisor must implement a supervisory pedagogical approach anchored in a socio-constructivist paradigm to accompany the student’s development while employing a reflective approach in coaching. In addition, these systems stress the importance of placing the student at the center of their learning, making them a real player in their own development.